Development Communication for Place Identity: Village Culture in the City of Semarang (Jurnal Komunikasi Pembangunan, 2020)
Development has caused the cut down of villages with historical and cultural values as the identity ofSemarang City. Using the Pentahelix Model, this study aims to determine how stakeholders of Semarangcity maintain the cultural values of villages as the identity of Semarang City. The study uses a qualitativedescriptive approach. Interviews and documentation are chosen as data collection techniques. The resultsshowed that the government, community, private sector, academia, and media had played an active role inconstructing the identity of Semarang City. However, each stakeholder has its own approaches inconstructing the identity of Semarang City. Collaboration between stakeholders still needs to be improvedso that there is mutual understanding regarding the definition and approaches in constructing the identityof Semarang City.